The Influence Of Leadership Style On Employee Performance Which Is Moderate By Motivation At The Public Works Department Of Bandar Lampung City - Habibullah Jimad; Muhammad Ibn Hajar (Green Inflation: International Journal of Management and Strategic Business Leadership, 2024)
This research aims to determine the effect of leadership style on employee performance with motivation as a moderating variable. This research used a sample of 195 employees of the Public Works Department in Bandar Lampung City. This research uses simple linear regression analysis and descriptive statistics which are processed using the SPSS version 23 statistical application. The results of this research show that the leadership style variable is proven to have a significant positive effect on employee performance variables and supports the first hypothesis. The motivation variable as a moderating variable in this study was proven to have no effect on the influence of the leadership style variable on employee performance and did not support the second hypothesis. Based on this, it can be concluded that this research supports the first hypothesis, but does not support the second hypothesis in this research.